Determining Factors that Influence Indonesian Consumers’ Sustainable Purchase Behavior - Glenito Yusuf Bagaskoro; Annisa Rahmani Qastharin (Journal of International Conference Proceedings (JICP), 2021)
Previous research has found a poor correlation between consumers' positive attitudes on sustainable purchasing and their actual purchasing behavior; this term can be referred to as an attitude-behavior gap. This study aims to identify factors that influence consumers' sustainable purchase behaviors and generate recommendations for a marketing approach. A survey has been done on 150 respondents, consisting of Millennials and Generation Z in Jabodetabek, Yogyakarta, and Bandung, with the utilization of Social Cognitive Theory (SCT). The study uses SEM-PLS Confirmatory Factor Analysis (CFA) to examine the results. The hypothesis test shows that Supportive Behavior for Environmental Organizations and Perceived knowledge about sustainability issues are the two most significant factors influencing consumers' sustainable behavior; besides that, Perceived Marketplace Influence is the only variable proven not positively to influence consumer sustainable behavior. These findings can be utilized to generate marketing approach recommendations for SMEs in Indonesia that apply sustainability value by paying more attention and make it more relatable to the variables that have proven to influence consumers' sustainable purchase behavior significantly.